Penggunaan Madu Topikal Efektif terhadap Penyembuhan Luka Kronis - Etty Etty; Yuliana Syam; Saldy Yusuf (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The aim of this study was to determine the effectiveness of topical honey in chronic wound healing. This research method uses a literature review method using five databases in search of articles, namely Pubmed, ProQuest, Science Direct, Wiley Online Library, and Google Scholar. The results of the literature review are from six research articles analyzed, five research articles showed that honey was effective against chronic wound healing compared to normal saline, povidone iodine and other therapies (p value <0.05), but one article was not statistically significant. In conclusion, the use of honey as a topical therapy which is effective in treating chronic wounds is due to the nutritional content or properties of honey. Keywords: Chronic Wounds, Honey, Wound Healing, Ulcers